Awareness towards rhesus isoimmunization and associated factors among reproductive age women at Debre Markos town, Ethiopia - Zewditu Mulualem; Yibelu Bazezew Bitewa; Genet Degu; Addisu Andualem Ferede (Elsevier, 2024)
Background: Rhesus isoimmunization is preventable by giving anti-rhesus D immune globulin during and after each pregnancy. There is limited evidence on the awareness of reproductive age group women about rhesus isoimmunization in the country Ethiopia. Objectives: This study is aimed at assessing awareness and associated factors towards Rhesus isoimmunization among reproductive age women in Debre Markos Town. Methods: A community-based cross-sectional study design was conducted at Debre Markos Town from December 1-30, 2022. Six hundred and five study subjects were selected using the multistage sampling technique. Data were collected by using an interviewer-administered, pretested, structured questionnaire. Data were entered into Epi-data version 4.2 and then exported to SPSS version 25 for further analysis. A binary logistic regression model was used. Variables with a p value of ≤ 0.05 in the multivariable logistic regression with a 95 % CI were declared statistically significant. The adjusted odds ratio was used to show the strength of the association between the dependent and independent variables. Results: Among the 605 respondents, 367 (60.7 %, 95 % CI; 56.9 %, 64.7 %) had poor awareness about rhesus isoimmunization. Women who can only read and write (AOR = 0.38, 95 % CI: 0.23, 0.65), completed primary school (AOR = 0.40, 95 % CI: 0.24, 0.68), secondary school (AOR = 0.40, 95 % CI; 0.24, 0.67), women who did not get health information (AOR = 0.50, 95 % CI; (0.33, 0.75), and average monthly income < 1500 Ethiopian birr (AOR = 0.44, 95 % CI; 0.27, 0.72) were significantly associated with awareness of rhesus isoimmunization. Conclusion and recommendation: The awareness of rhesus isoimmunization among reproductive age group women was low. Hence, the concerned and responsible bodies should be given an emphasis on those groups of women and create awareness about rhesus isoimmunization.